PERFORMANCE OF RED CHILI PEPPER IN NORTH SUMATERA CASE: BERINGIN DISTRIC, DELI SERDANG REGENCY - Nasution, Amelira Haris (Jurnal Pertanian, 2019)
Red chili pepper is an important commodity for the people of Indonesia. Therefore the government has set red chili pepper as a strategic commodity with a production target of 2.29 million tons in 2019. One of the centers of red chili pepper production is North Sumatera. As a production center, the problem is usually about the low prices at the farm level.  This is due to the lack of a marketing channel role analysis that could accommodate farmers' aspirations, causing farmers to not have bargaining power, so farmers are only a "price taker”. The purpose of this study is to analyze the red chili pepper marketing system through marketing channel analysis, marketing channel role analysis and operational efficiency analysis through marketing margins and farmer shares. This study was conducted from June 2019 until August 2019 in Beringin District, Deli Serdang Regency, North Sumatra. Farmers were selected using purposive sampling methods, and middlemen were chosen by using the snowball sampling method. In processing data this study uses descriptive qualitative and quantitative analysis. The results showed that there were 3 channels in marketing red chili pepper. Based on the results of the efficiency analysis it was found that marketing channel 2 was the most efficient channel due to several things, such as the existence of cooperation with the collector and the unavailability of other marketing institutions that favored the red chili pepper farmers. In order to improve bargaining power, farmers need to strengthen the existing STA to be able to reach all red chili farmers.